Dual-wavelength mode-locked Tm3+-doped fiber laser at 2 μm region with controllable soliton pulse number by employing graphene on microfiber. (September 2018) - Yang, Guang; Liu, Yange; Wang, Zhi; Wang, Guangdou; Wang, Zhenhong; Wang, Xiaoqing
Highlights: A dual-wavelength mode-locked fiber laser working in 2-μm region is proposed. Controllable soliton pulse number in the dual-wavelength lasing is observed. Graphene on microfiber is the key component to achieve the dual-wavelength laser. Abstract: We demonstrate the generation of dual-wavelength ultrafast Tm 3+ -doped fiber laser at 2 μm region based on graphene saturable absorber. A section of graphene film is transferred on a microfiber, which allows light-graphene interaction via evanescent field. Due to the cavity birefringence-induced comb filter, dual-wavelength mode-locking at 1932/1981 nm region is obtained. The number of soliton pulses at 1932 nm region can be controlled by adjusting the pump power and the pulse trains at 1981 nm region remain the soliton state at fundamental repetition frequency 20.65 MHz. By tuning the polarization controller (PC) under proper pump power, dual-wavelength soliton/four-soliton operation centered at 1927.04/1977.94 nm is also experimentally investigated.